2010
DOI: 10.1111/j.1478-3231.2010.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of spontaneous bacterial peritonitis in cirrhotic patients non-prophylactically treated with norfloxacin: serum albumin as an easy but reliable predictive factor

Abstract: Spontaneous bacterial peritonitis was associated with high sepsis-related mortality in cirrhotic patients. Serum albumin before discharge was a useful single parameter to predict the recurrence of SBP and long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
4
28
1
Order By: Relevance
“…The in‐hospital mortality in this group in our study was 32%, almost comparable to the reported mortality of 39% by Huang et al . .…”
Section: Discussionmentioning
confidence: 99%
“…The in‐hospital mortality in this group in our study was 32%, almost comparable to the reported mortality of 39% by Huang et al . .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Huang CH et al, using the cutoff point for serum albumin level of 2.85 g/dl as a predictor for recurrence of SBP, the sensitivity was 70.2% and the specificity was 76.3%. 14 Weinstein MP, et al studied 28 cases of spontaneous bacterial peritonitis over a period of 5 years and found that mortality was considerably higher in patients with serum albumin lower than 2.5 g/dl. It is suggested from these studies that serum albumin < 2.5gm/dl is significantly associated with adverse prognostic effects, for instance recurrence of SBP and mortality rate is increased.…”
mentioning
confidence: 99%
“…Patients with cirrhosis are susceptible to a variety of complications, and their life expectancy can be markedly reduced, especially in those with acute on chronic liver failures23. Infections, especially bacterial infections, account for the major causes for decompensating liver cirrhosis4 or acute on chronic liver failure, and contribute towards high morbidity and mortality of these patients56.…”
mentioning
confidence: 99%